Pengembangan Media Treasure Hunt pada Pembelajaran Matematika Madrasah Ibtidaiyah Miftahul Huda Nglegok Blitar - Puji Asmaul Chusna; Khasanah Khasanah; Ermalistiani Ermalistiani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study was used to determine the feasibility and effectiveness of the development of learning media used to solve the problem of understanding mixed arithmetic operations in a relaxed and fun way. With this goal in mind, the researcher uses the Research And Development (R and D) method by developing the Treasure Hunt media using the Borg and Gall research procedure that uses 6 development steps. In this development method obtained validation results from 3 validators namely material experts as much as 84%, media experts as much as 94%, and subject experts as much as 95% of the assessment can be categorized that the media developed is very valid. The attractiveness aspect can also be categorized as very valid because it gets a percentage of 92.2%. This is also proven again through the acquisition of the results of the pre-test (61.94) and post-test (80.27) which can be concluded that Ho is rejected and Ha is accepted.